Active Tracking-based cardiac triggering for MR-thermometry during radiofrequency ablation therapy in the left ventricle - Mooiweer, Ronald; Schneider, Rainer; Krafft, Axel Joachim; Empanger, Katy; Stroup, Jason; Neofytou, Alexander Paul; Mukherjee, Rahul K.; Williams, Steven E.; Lloyd, Tom; O'Neill, Mark; Razavi, Reza; Schaeffter, Tobias; et al. (Frontiers in Cardiovascular Medicine, 2022)
Cardiac MR-thermometry shows promise for real-time guidance of radiofrequency ablation of cardiac arrhythmias. This technique uses ECG-triggering which can be unreliable in this situation. A prospective cardiac triggering method was developed for MR-thermometry using the active tracking (AT) signal measured from catheter microcoils. In the proposed AT-based cardiac triggering (AT-trig) sequence, AT modules were repeatedly acquired to measure the catheter motion until a cardiac trigger was identified to start cardiac MR thermometry using single-shot echo-planar imaging. The AT signal was bandpass filtered to extract the motion induced by the beating heart and cardiac triggers were defined as extremum (peak or valley) of the filtered AT signal. AT-trig was evaluated in a beating heart phantom and in-vivo in the left ventricle of a swine during temperature stability experiments (6 locations) and during one ablation. Stability was defined as the standard deviation over time. In the phantom, AT-trig enabled triggering of MR-thermometry and resulted in higher temperature stability than an untriggered sequence. In all in-vivo experiments AT-trig intervals matched ECG-derived RR-intervals. Mistriggers were observed in 1/12 AT-trig stability experiments. Comparable stability of MR-thermometry was achieved using peak AT-trig (1.0±0.4°C), valley AT-trig (1.1±0.5°C) and ECG triggering (0.9±0.4°C). These experiments show that continuously acquired AT signal for prospective cardiac triggering is feasible. MR-thermometry with AT-trig leads to comparable temperature stability as with conventional ECG-triggering. AT-trig could serve as alternative cardiac triggering strategy in situations where ECG triggering is not effective.